Development of Offset-Based Printing Business Model - Zulkarnain; Afifa, Hidayathul; Silvia, Deli (Indonesian Journal of Business and Entrepreneurship, 2022)
The application of a business model in offset printing is one of the keys to facing competition. The tight competition is not only limited to the quality of the prints produced, but also to customer service and market gain. The purpose of this research is to develop an offset-based printing business model. The analysis was carried out using the Business Model Canvas (BMC) and strength-weakness-opportunity-threats (SWOT) approaches. Data were obtained based on literature studies, field observations, and expert interviews. BMC is used to model the offset-based printing business development. While the SWOT approach is used to analyze internal and external factors that affect the offset-based printing business. The results of this study have obtained 13 elements that need to be applied to the printing business. It is time for an offset-based printing business model to shift from one that concentrates on production to one that focuses on the digital market, both through websites and social media applications. Keywords: business model, BMC, offset printing, SWOT, digital market